Interfaces of domestic violence and organization: Gendered violence and inequality. Issue 2 (15th September 2020) - Wilcox, Tracy; Greenwood, Michelle; Pullen, Alison; O'Leary Kelly, Anne; Jones, Deborah
Abstract : Domestic violence is a global pandemic. Domestic violence is gendered violence and perpetuates women's inequality. Women experience domestic violence at higher rates than men, and the perpetrators are, more often than not, men. Organizations play an essential role in addressing domestic violence. This article establishes the relationship between domestic violence and organizations at four interfaces of contemporary relevance, to make visible the ways in which domestic violence sustains gender inequality. Interfaces that are central to problematizing domestic violence and organization are discussed: domestic–work; business–society; men–women; and mind/rationality–body/emotion. Adopting the heuristic of interfaces draws our attention to the boundaries that separate fields but also that which connects them, enabling multidisciplinary research across domestic violence to be reviewed in a way that surfaces both the complexities and the organizational responsibility for action‐based change in practice and scholarship. The article concludes by calling for future research that transcends practice and scholarship.